Modelo de producción agrícola familiar socio-ecológicamente eficiente para mejorar el retorno económico en la asociación de productores agropecuarios Río Peripa - Barrionuevo Manzano, Juan Carlos (2018)
The Ecuadorian agricultural production system is constituted by the Business Agriculture and the Peasant Family Agriculture; within the Peasant Family Farming segment, is the productive activity developed by the Peripa River Agricultural Producers Association, who resort to the leasing of land and production in small properties, where different productive skills are expressed and their agricultural potential varies enormously. Some of them, as well as the crops that grow there, also vary, but their common characteristic is the low economic return they receive from their productive activity. From the direct observation, two survey formats were designed: The socioeconomic survey that seeks to identify the main aspects concerning the income and expenses of the families and the Socio Ecological survey, seeks to identify the interrelation and associative efforts of the organization. as the relevance of the environmental aspect in it. With the information obtained and through an approximation of the Integrated Multi-scale Analysis Method of the Metabolisms of the Societies, Musiasem, the system can be summarized in a graphical-numerical scheme, whose essential characteristics are weighted in a matrix that allows to grade the phenomena observed in the order of the intensity of attention required by it. The results achieved demonstrate the progressive consolidation of the consumption model in the study population, which results in a relative surplus of productive factors and a significant expenditure of monetary resources for the acquisition of food and other items. Later, with the application of a socially efficient model, one can observe the improvement of the economic return of the families of the associated producers and the systematic reduction of the environmental impact generated by the traditional production model characterized by the monoculture tendency, the indiscriminate use of biosides and chemical fertilizers, the abandonment of community practices and the loss of their food sovereignty.